Advances in lead‐free high‐temperature dielectric materials for ceramic capacitor application. Issue 1 (26th April 2018) - Jia, Wenxu; Hou, Yudong; Zheng, Mupeng; Xu, Yuru; Zhu, Mankang; Yang, Kuiyong; Cheng, Huarong; Sun, Shuying; Xing, Jie
Abstract : Ceramic capacitors with upper operating temperatures far beyond 200°C are essential for high‐temperature electronics used in deep oil drilling, aviation, automotive industry and so on. Recent advances in existing lead‐free dielectrics for potential high‐temperature capacitor applications are reviewed and grouped into three categories according to the parent component of the solid solution. Their desirable temperature stabilities were summarised comprehensively. However, there are still some limitations in the current research, such as achieving low loss in a wide temperature range and maintaining stable dielectric properties with different frequencies or at different voltages. Furthermore, the successful implementation of multilayer ceramic capacitors is one of the biggest challenges, which will have far‐reaching impacts on the realisation of high‐temperature capacitor application in the future.